Designing a microcontroller-based half-duplex interface device drove by the touch-tone signal - Arief Goeritno; Ika Setyawibawa; Dwi Suhartono (JURNAL INFOTEL, 2021)
The interface device for communicating (IDC) as a bridge for the merger between two different systems based on different protocols and standards can be made of several electronic modules. The two Arduino boards (UNO R3 and MEGA2560 R3) have been constructed as the electronic modules of a gateway become a haft-duplex IDC, and are driven by the touch-tone signal. The research objectives, i.e., assembling some of the hardware for the embodiment of the adapter system, making a program structure, and performing a test of the IDC system. The haft-duplex IDC has been carried out by integrating all components by wiring to form an embedded system. Then, programming the microcontroller modules based on the Arduino software is carried outin six stages. Finally, the simulation test with the provision of conditions is carried out and obtained of six conditions for (i) the circuit of ring detection, (ii) the circuit of voice-operated transmit, (iii) the circuit off/on the hook of the telephone module, (iv) the circuit of tone decoder, (v) dial-up telephone numbers via push buttons and switching IC circuits, and (vi) the circuits of voice recording and storage in the form to playback. The test's success with six conditions has been an indication that the microcontroller-based IDC system is functioning as expected. Completing, the conclusion, and recommendationsrelated to measurement on the various purposes and the real conditions for the half-duplex interface adapter can be implemented.